2016
DOI: 10.1093/sleep/zsw075
|View full text |Cite
|
Sign up to set email alerts
|

An Aggregate Measure of Sleep Health Is Associated With Prevalent and Incident Clinically Significant Depression Symptoms Among Community-Dwelling Older Women

Abstract: An aggregate, multidimensional measure of sleep health was associated with both prevalent and incident clinically-significant depression symptoms in a gradient fashion. Future studies are warranted to extend these findings in different populations and with different health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 46 publications
8
70
0
Order By: Relevance
“…The cutoff values for sleep duration were notably shorter than previous reports. Our results indicated that 5 h 20 min-7 h 6 min represented "good" sleep duration whereas other studies have used values of 7-8 h [7], 6-8 h [3][4][5], and 7-9 h [6]. However, actigraphy was used to measure sleep in the present study, while sleep durations were self-reported in prior studies of sleep health.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The cutoff values for sleep duration were notably shorter than previous reports. Our results indicated that 5 h 20 min-7 h 6 min represented "good" sleep duration whereas other studies have used values of 7-8 h [7], 6-8 h [3][4][5], and 7-9 h [6]. However, actigraphy was used to measure sleep in the present study, while sleep durations were self-reported in prior studies of sleep health.…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have used sleep latency and wake after sleep onset to operationalize the sleep efficiency dimension of sleep health. In these studies, less than 30 min of sleep latency [6] or combined sleep latency and wake after sleep onset [3][4][5] is considered to be consistent with "good" sleep continuity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulating evidence suggests that, beyond sleep duration alone, each of these sleep health dimensions are individually associated with health risks (9). More importantly, aggregate or composite measures of sleep health are associated in a graded fashion with health risks (10).…”
mentioning
confidence: 99%